Efficacy of Silver Dihydrogen Citrate and Steam Vapor against a Human Norovirus Surrogate, Feline Calicivirus, in Suspension, on Glass, and on Carpet - Buckley, David (Appl Environ Microbiol, 2018)
Carpets and other soft surfaces have been associated with prolonged and reoccurring human norovirus (HuNoV) outbreaks. Environmental hygiene programs are important to prevent and control HuNoV outbreaks. Despite our knowledge of HuNoV transmission via soft surfaces, no commercially available disinfectants have been evaluated on carpets. Our aim was to adapt a current standardized method for virucidal testing by assessing two disinfection technologies, silver dihydrogen citrate (SDC) and steam vapor, against one HuNoV surrogate, feline calicivirus (FCV), on wool and nylon carpets. First, we evaluated the effect of both technologies on the appearance of carpet. Next, we evaluated the efficacy of SDC in suspension and the efficacy of SDC and steam vapor against FCV on a glass surface, each with and without serum. Lastly, we tested both technologies on two types of carpet, wool and nylon. Both carpets exhibited no obvious color changes; however, SDC treatments left a residue while steam vapor left minor abrasions to fibers. SDC in suspension and on glass reduced FCV by 4.65 log(10) and >4.66 log(10) PFU, respectively, but demonstrated reduced efficacy in the presence of serum. However, SDC was only efficacious against FCV on nylon (3.62-log(10) PFU reduction) and not wool (1.82-log(10) PFU reduction). Steam vapor reduced FCV by >4.93 log(10) PFU on glass in 10 s and >3.68 log(10) PFU on wool and nylon carpet carriers in 90 s. There was a limited reduction of FCV RNA under both treatments compared to that of infectivity assays, but RNA reductions were higher in samples that contained serum. IMPORTANCE Human noroviruses (HuNoV) account for ca. 20% of all diarrheal cases worldwide. Disease symptoms may include diarrhea and vomit, with both known to contribute to transmission. The prevention and control of HuNoV are difficult because they are environmentally resilient and resistant to many disinfectants. Several field studies have linked both hard and soft surfaces to HuNoV outbreaks. However, many disinfectants efficacious against HuNoV surrogates are recommended for hard surfaces, but no commercially available products have demonstrated efficacy against these surrogates on soft surfaces. Our research objectives were to evaluate liquid and steam-based technologies in suspension and on hard surface carriers in addition to adapting and testing a protocol for assessing the virucidal effects of disinfection technologies on carpet carriers. These results will inform both the government and industry regarding a standard method for evaluating the virucidal effects of disinfectants on carpet while demonstrating their efficacy relative to suspension and hard-surface tests.